Transformational Leadership and Organizational Citizenship Behavior: Insights from Buddhist Religious Organizations - Nyanabhadra, Phap Tu; Darma, Fendi; Elvinsia, Elvinsia; Apriyono, Dito; Ginarsih, Ginarsih; Mudjiarto, Hari; Ardianto, Hendri (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
This study aims to analyze the influence of transformational leadership on organizational citizenship behavior (OCB) in Buddhist assembly organizations. The problem lies in the lack of understanding of the unique characteristics of Buddhist organizations, such as spiritual orientation and community values. The approach used is quantitative and survey methods, data is collected from 117 respondents who are active members of the organization. The research instrument was in the form of a validated questionnaire, while data analysis was carried out by a simple linear regression test using SPSS. The results show that transformational leadership has a significant influence on OCB, with the inspirational motivation dimension being the dominant factor in encouraging proactive and voluntary behavior of members. These findings emphasize the importance of vision, interpersonal communication, and individual attention in increasing organizational member engagement.